3rd lnternational Conference on Aerogels tor Biomedical and Enviornmental Applications: Book of Abstracts (University of Maribor Press, 2023)
The 3rd lnternational Conference on Aerogels for Biomedical and Environmental Applications, organized by the Faculty of Chemistry and Chemical Engineering University of Maribor and the AERoGELS COST Action, presented the latest research results and applications of aerogels. This publication compiles the abstracts of the conference and highlights the main results and innovations. The abstracts address the use of aerogels in medical, pharmaceutical, and food applications, including drug delivery systems, scaffolds tor tissue engineering, and bioactive coatings. They also explore aerogels as catalysts, insulators, and environmental solutions and investigate improved catalytic activity and thermal insulation properties. The abstracts emphasize interdisciplinary collaboration and provide ideas tor future research directions. This publication provides valuable insights tor researchers and industry professionals interested in harnessing the remarkable properties of aerogels for biomedical and environmental purposes.